THE ROLE OF INFORMATION PROCESSING IN DEVELOPING COGNITIVE-PRAGMATIC COMPETENCIES OF FUTURE TEACHERS - Tо‘rаbekоvа Аzizа Mirzаbek qizi (International Journal of Literature and Language Studies, 2026)
This article, based on a theoretical analysis of scientific research and international projects conducted by numerous domestic and foreign scientists, reveals the role of information processing in developing cognitive-pragmatic competencies of future teachers. The concept of information and working with various types of information content are explored, along with the issues of protection from negative information influence and ensuring the information-psychological security of individuals. These topics have been examined in both domestic and foreign scientific works, with attention also given to the concept of “cognitive information theory”.